(untitled) (Research, Society and Development, 2025)
Neurocysticercosis is an infectious disease of the central nervous system caused by Taenia solium. Bali is an endemic area for neurocysticercosis and is associated with the consumption of raw pork. Clinical manifestations of neurocysticercosis vary, ranging from mild to fatal. Therefore, it is important to recognize the symptoms to ensure appropriate therapy and improve patient outcomes. The current study aims to report a clinical case of a 64-year-old woman who presented with a sudden onset of dizziness for four days, which she felt upon waking. Other complaints included mild headache and nausea. She had no medical history, but she had frequently consumed pork, most recently 10 days ago. Bidirectional nystagmus was observed. A CT scan of her head revealed several focal lesions suggestive of a worm infestation. She was diagnosed with neurocysticercosis and was treated with oral albendazole, dexamethasone injection, oral folic acid, and pantoprazole injection. She reported improvement after treatment. This case demonstrates an atypical presentation of neurocysticercosis and clinical improvement after initiation of an appropriate therapeutic protocol. This case emphasizes the importance of suspecting neurocysticercosis in endemic areas with a history of exposure, even if the clinical manifestations are atypical.